Etiology of Severe Pneumonia in Children in Alveolar Lavage Fluid Using a High-Throughput Gene Targeted Amplicon Sequencing Assay - Li, Fei; Wang, Yin; Zhang, Yuhan; Shi, Peng; Cao, Linfeng; Su, LiYun; Zhu, Qiguo; Wang, Libo; Lu, Roujian; Tan, Wenjie; Shen, Jun (Frontiers in Pediatrics, 2021)
Objective: To evaluate the diagnostic value of a high-throughput gene targeted amplicon sequencing (TAS) assay for detecting pathogenic microorganisms in alveolar lavage fluid (ALF) from children with severe community-acquired pneumonia (SCAP). Methods: A retrospective study was performed on 48 frozen ALF samples from 47 severe pneumonia cases admitted to Children's Hospital of Fudan University from January 1, 2019 to March 31,2019. All samples were tested by a multiplex PCR (Multi-PCR) assay and a TAS assay. The results of the TAS panels were parallel compared with Multi-PCR and Conventional Tests (CT) including culture ,direct fluorescent antibody method (DFA), and singleplex polymerase chain reaction (PCR). Results: The proportion of pathogens detection by CT was 81.2% (39/48). The 8 common respiratory including respiratory syncytial virus (RSV), adenovirus (ADV), influenza A virus (FLUA), influenza B virus (FLUB), parainfluenza virus 1-3 (PIV1-3) and human Metapneumovirus (hMPV) were found in 31.2% (15/48) of the 48 samples by DFA. With the criteria of CT results used as “Golden Standard” for determing of TAS results, the proportion of pathogens detection by TAS was 70.8% (34/48). The difference of proportion of pathogens detection between TAS and CT was not statistically significant (p =0.232). The sensitivity and specificity of TAS for pathogens detection based on CT were 87.1% (95%CI, 71.77-95.18%) and 100.0% (95%CI, 62.88-100%), the positive predictive value (PPV) and negative predictive value (NPV) were 100.0% (95%CI，87.35-100%) and 64.2% (95%CI，35.62-86.02%) , respectively. While Multi-PCR results were used as “Golden Standard”, the total pathogens detection rate of TAS was 83.3% (40/48), which had a significant difference with that of Multi-PCR (p =0.003). The sensitivity and PPV of TAS compared with Multi-PCR were 83.3% (95%CI, 69.23-92.03%) and 100.0% (95%CI, 89.08-100%), respectively. High rates of co-infection were proved by CT, Multi-PCR and TAS. Mycoplasma pneumoniae (MP) and ADV were the two most frequently detected pathogens in all three assays. Conclusion: Compared with the CT and Multi-PCR methods, this TAS assay had a good performance in detecting bacteriological and viral pathogens from ALF. More researches were needed to establish interpretation criteria based on TAS reads or analysis platforms.